Training and Assistance in Tablet Manufacturing and Tablet Quality Control - Wibowo, Teguh Setiawan; Sari, Diah Indah Kumala; Negara, Sri Bintang Sahara Mahaputra Kusuma (Jurnal Pengabdian Masyarakat Bestari, 2024)
Giving drug to patients or people who have been diagnosed with a disease is very rarely given as a pure active ingredient so most drugs are given in a dosage form. One form of drug dosage preferred by adult patients is a solid dosage form in the form of tablet. The aim is to increase understanding and technical abilities of pharmacy students in tablet manufacturing and tablet quality control. The method used was theoretical, practical and final evaluation which was carried out on 18 pharmacy students in the Pharmaceutical Technology Laboratory on the Universitas Muhammadiyah Lamongan. The result was the community service activities through training in tablet making and tablet quality control received enthusiasm and good responses from a total of 18 students participating. It is hoped that this training activity will be the beginning of opening up collaboration between the campus and private companies that make legal medicines and state-owned companies in expanding information and knowledge regarding tablet manufacturing and tablet quality control.